The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsami.9b19746
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Spirothienoquinoline-Based Small Molecules for Organic Photovoltaic and Organic Resistive Memory Applications

Abstract: A new electron-rich spirothienoquinoline unit, t BuSAF-Th, has been developed via incorporation of a thienyl unit instead of a phenyl unit into the six-membered ring of the spiroacridine (SAF) and utilized for the first time as a building block for constructing small-molecule electron donors in organic solar cells (OSCs) and as active layers in organic resistive memory devices. The resulting three-dimensional spirothienoquinoline-containing 1–4 exhibit high-lying highest occupied molecular orbital (HOMO) ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…As a final test, the optimal ϵV H V P +rVGG model has been applied (Figure and Tables S6 and S7) to a series of 30 organic photofunctional materials reported by Yam and co-workers. These test molecules are not included in the CSD data set. In addition to the high correlation ( r > 0.95, Figure b and c), the ML-predicted excited-state energies for both low-lying singlet and triplet states exhibit notably low MAEs (<0.14 eV, Figure d) in comparison to the PBE0-computed references.…”
Section: Resultsmentioning
confidence: 99%
“…As a final test, the optimal ϵV H V P +rVGG model has been applied (Figure and Tables S6 and S7) to a series of 30 organic photofunctional materials reported by Yam and co-workers. These test molecules are not included in the CSD data set. In addition to the high correlation ( r > 0.95, Figure b and c), the ML-predicted excited-state energies for both low-lying singlet and triplet states exhibit notably low MAEs (<0.14 eV, Figure d) in comparison to the PBE0-computed references.…”
Section: Resultsmentioning
confidence: 99%
“…The lower band gap of CB films suggested a more vital CT ability in the film state to promote charge carrier migration. To better comprehend the UV–vis spectra, the time-dependent density-functional theory (TD-DFT) calculations were performed using the GGA/BLYP function. The specific absorption positions and intensities are presented in Figure S12, and the corresponding descriptions of the first 12 singlet–singlet electronic transition features are provided in Table S1. These results demonstrated that the high-energy absorption band corresponds to electronic transitions from LUMO to LUMO + 2 and LUMO + 3, while the ICT effect of CB could be attributed to the LUMO-to-LUMO + 1 transition …”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the current declined sharply at −3.6 V from 6.1 × 10 –2 to 2.2 × 10 –5 A, when the device underwent a negative sweep from 0 to −5 V, indicating a reverse course from the HCS to LCS state. This transition represented that the stored information can be readily erased, revealing a Flash-type behavior. Notably, the nanofiber-based device could realize the ON/OFF transformation by switching the positive or negative applied voltage. Given that the film thickness of the active medium layer is also an important factor in controlling the electrical properties of the memristor.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) The nitrogen atoms in terpyridine group exhibit strong coordination ability with transition metals, which can enhance the thermostability and conductivity of organic semiconductors; [ 18 ] (c) Metal Co(II) as the central atom has good redox activity to offer two or more electrical stable states; [ 19 ] and (d) The distinct molecular structures between organic ligand and OSMCs help to induce the variable memory characteristics and figure out information‐storage mechanism. [ 20 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%